Safety and efficacy revisited: a systematic review and meta-analysis of glue versus tack mesh fixation in laparoscopic inguinal herniorrhaphy - Raja, Sandesh; Raja, Adarsh; Ansari, Ziyan; Eman, Sara; Bajaj, Simran; Ahmed, Muhammad; Kumar, Uday; Shah, Yawar Hussain; Jawahar, Sachin; Aftab, Faisal; Rajani, Deepak; Kumar, Satesh; et al. (Frontiers in Surgery, 2024)
This analysis addresses the uncertainty surrounding the efficacy of Glue Mesh Fixation (GMF) compared to Tack Mesh Fixation (TMF) in laparoscopic herniorrhaphy. Our meta-analysis incorporates new randomized controlled trials (RCTs) to enhance the reference for assessing the efficacy and safety of GMF.PubMed, Google scholar, Science direct and Cochrane library were thoroughly checked for articles in the English language performed from inception till May 2023 using the keywords "Glue mesh repair", "Tack mesh repair", "Inguinal Hernia", "Herniorrhaphy", "Laparoscopic", "Mesh Fixation", and "Randomized controlled trials".In this meta-analysis, we incorporated a total of 20 randomized controlled trials, evaluating each article individually using quality ratings. Compared to TMF, GMF demonstrated a significant reduction in the incidence of chronic pain (RR: 0.40, [0.23, 0.68]) and pain scores on postoperative day one (MD: -1.07, [-1.90, -0.25]). We also used funnel plots and Egger's regression to test for publication bias.In summary, this meta-analysis establishes the significance of GMF in reducing chronic pain and postoperative day one pain compared to TMF. However, no statistically significant difference was noted between GMF and TMF groups concerning hematoma, seroma, operation time, recurrence rate, and total complications. Nonetheless, given the small number of cases in this study, it is critical that the findings be validated in the future by multicenter, large-sample, high-quality RCTs.